The Influence of Supporting Facilities, the Quality of Health Center Services, and the Competence of Medical Personnel on Patient Satisfaction Levels - Hendarini, Yayak; Setiawan, Riyanto; Herlambang, Toni (Proceedings Series on Social Sciences & Humanities, 2025)
In an era of increasingly competitive and high-quality health services, patient satisfaction is one of the main indicators of the success of a health facility. One of the key factors that affect the level of patient satisfaction is the competence of medical personnel which includes technical skills, professional attitudes, and interpersonal skills in providing services. Good medical personnel competence not only ensures proper and effective service, but is also able to build trust and comfort for patients during the treatment process. This study aims to analyze the influence of supporting facilities, service quality, and competence of medical personnel on patient satisfaction levels. The three variables are measured through key indicators such as the completeness and comfort of facilities, the dimensions of service quality (tangibles, reliability, responsiveness, assurance, and empathy), and the competence of medical personnel which include work quality, quantity of work, punctuality, responsibility, and initiative. The research method uses a quantitative approach with a cross-sectional design and involves a sample of patients from various healthcare facilities. The results of the analysis showed that supporting facilities, service quality, and competence of medical personnel positively and significantly affected patient satisfaction. Adequate facilities provide comfort, good service quality increases patient trust and security, and competent medical personnel are able to provide appropriate services and build good relationships with patients. These findings are in line with previous studies that affirm the importance of these three factors in improving patient satisfaction. This research provides important implications for health facility managers to continue to improve facilities, service quality, and competence of medical personnel to achieve optimal patient satisfaction levels and support the success of health services in a sustainable manner.